EFFECT OF PHOSPHORUS AND ZINC ON GROWTH AND YIELD OF SUMMER GROUNDNUT (Arachis hypogaea L.) - GULAM MASTHAN VALI; SHIKHA SINGH; DHULIPALLA SAI VASAVI SRUTHI; NARREDDY HINDUJA; VIKAS TALASILA; DHANANJAY TIWARI. (The Bioscan, 2020)
A field experiment was conducted in the crop research farm of SHUATS, Prayagraj to know the effect of Phosphorus and Zinc on growth and yield of Summer groundnut. The experiment consisted of 12 treatments which includes three levels of Phosphorus (30, 40 and 50 kg/ha) and four levels of Zinc (0, 20, 25 and 30 kg/ha). The treatment receiving 50 kg Phosphorus + 30 kg Zinc/ha produced significantly higher plant height (35.58 cm), Pod yield (3.24 t/ha), total number of pods/plant (29.56) and 100 kernel weight (39.35 g). However, Net returns (139103.93 rs/ha) and B: C ratio (1.80) was also obtained maximum with the application of 50 kg phosphorus + 30 kg Zinc/ha. This experiment shown treatment receiving 50 kg Phosphorus + 30 kg Zinc/ha was more productive and economic.